3D AR Learning Media on Human Respiratory Organs to Train Elementary Science Process Skills - Hayyuna, Ristafani; Kurniawan, Dede Trie; Lestari, Triana (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
The background of this research was carried out because there was no application of digital media in schools and only used media in the form of books. At this time there is a great need for learning media that is interactive, interesting, and motivates students so that learning in the classroom becomes fun. However, the learning media used is only conventional media, especially in learning the material of the respiratory organs in humans. Through this statement, researchers plan to design and develop 3D Augmented Reality learning media based on the characteristics of grade V students of SDN 068 Sindanglaya. This study was made to determine the science process skills of students with the subject matter of human respiratory organs using 3D Augmented Reality learning media. The research method used is the Weak Experiment method with One-Group pretest-posttest Design. The results of the media feasibility test based on teachers, student responses and observation questionnaires of science process skills obtained an average percentage of 92.6% which indicates the category "Very Feasible". So it can be concluded that the 3D Augmented Reality learning media of respiratory organ material in humans is very feasible to use in the learning process in the classroom to train students' science process skills.